2005
DOI: 10.1086/426916
|View full text |Cite
|
Sign up to set email alerts
|

A 4.8 and 8.6 GHz Survey of the Large Magellanic Cloud. I. The Images

Abstract: Detailed 4.8 and 8.6 GHz radio images of the entire Large Magellanic Cloud with half-power beamwidths of 33 00 at 4.8 GHz and 20 00 at 8.6 GHz have been obtained using the Australia Telescope Compact Array. A total of 7085 mosaic positions were used to cover an area of 6 on a side. Full polarimetric observations were made. These images have sufficient spatial resolution ($8 and 5 pc, respectively) and sensitivity (3 of 1 mJy beam À1 ) to identify most of the individual supernova remnants and H ii regions and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 17 publications
(21 reference statements)
0
58
0
Order By: Relevance
“…The WR region appears to be similar to the 30 Doradus (Tarantula Nebula), which also dominates the Hα (Gaustad et al 2001), far-IR (Meixner et al 2006), and radio (Dickel et al 2005) emission of the LMC, as shown in Fig. 7, but it contributes very little to total stellar mass.…”
Section: Dust and Star Formation In The Wr Region: High Densitymentioning
confidence: 89%
See 1 more Smart Citation
“…The WR region appears to be similar to the 30 Doradus (Tarantula Nebula), which also dominates the Hα (Gaustad et al 2001), far-IR (Meixner et al 2006), and radio (Dickel et al 2005) emission of the LMC, as shown in Fig. 7, but it contributes very little to total stellar mass.…”
Section: Dust and Star Formation In The Wr Region: High Densitymentioning
confidence: 89%
“…7. Mosaic of the images of the Large Magellanic Cloud (Gaustad et al 2001;Meixner et al 2006;Dickel et al 2005). North is up and east is to the left.…”
Section: Dust and Star Formation In The Wr Region: High Densitymentioning
confidence: 99%
“…To this end, extensive mappings of the MCs have recently been conducted at a number of wavelengths. Surveys have been made in H I emission at 21-cm (HIPASS: Barnes et al 2001;Brüns et al 2005;Staveley-Smith et al 1997Stanimirović et al 1999;and Muller et al 2003), in molecular spectral CO lines (NANTEN: Fukui et al 1999;Mizuno et al 2001), as well as in the radio continuum (Haynes et al 1991;Dickel et al 2005), in the thermal infrared (IRAS: Beichman et al 1988;MSX: Mill et al 1994;SAGE: Meixner et al 2006; S 3 MC: Bolatto et al 2007), in the nearinfrared (DENIS: Epchtein et al 1997;2MASS: Skrutskie et al 2006), in broadband optical colors (MCPS: Zaritsky et al 2002Zaritsky et al , 2004 as well as in optical emission lines (MCELS: Smith et al 1998), and at ultraviolet (Smith, Cornett & Hill 1987) and X-ray wavelengths (ROSAT: Snowden & Petre 1994; Chandra and ACIS: Townsley et al 2006). While these surveys have deepened our understanding of the Clouds themselves -e.g., their star formation history, their stellar content, and their overall structure (van der Marel 2001) -the H I investigations are central to understanding the most obvious product of the MW-MC interaction -the Magellanic Stream.…”
Section: Introductionmentioning
confidence: 99%
“…Radio-continuum surveys were predominately based on observations from the Aus- as well as the 6 cm and 3 cm mosaics published by Dickel et al (2005); Wong et al (2012). In addition, a 36 cm Molonglo Synthesis Telescope (MOST) mosaic image (as described in Mills et al 1984) was used.…”
Section: Magellanic Clouds Surveysmentioning
confidence: 99%